PENINGKATAN NILAI OVERALL EQUIPMENT EFFECTIVENESS (OEE) MESIN INJECTION MOLDING DI PERUSAHAAN BEVERAGE PACKAGING - Jumattul Koip (Universitas Mercu Buana, 2018)
Increased investment in the beverage industry sector has boosted the growth of the beverage industry while impacting the size of beverage packaging needs in Indonesia. PT. Indo Tirta Abadi as a company engaged in beverage packaging supply chains for the largest beverage companies in Indonesia seeks to maximize the company's performance to become the leading beverage packaging manufacturer in Indonesia. The problem is that the Injection Husky-8 engine that produces PET-Preform as the company's flagship product has increased the number of pending products and caused losses for the company. The aim of this study was to improve the achievement of OEE on the 8-Husky Injection machine. Analysis of the six big losses and fishbone diagrams is used to identify losses and their causes, then FMEA and 5W1H are used as tools to determine priority recommendations for improvements based on the level of risk of causing losses. The existing OEE value of Injection machines is 92.40%. This achievement is quite good when compared to word-class OEE but has not yet achieved the company's target. Based on the analysis, the dominant factors that have not achieved the OEE target are defects in process & rework and reduced speed. Priority improvements are needed, namely overcoming the crust of the barrel material and the burning runner at start-up, overcoming the high tower cooling temperature, and overcoming high feed temperature by purging with undried resin during engine startup, periodic cleaning and maintenance processes on the cooling unit tower, and install Premixer in feedthroath.